THE IMPACT OF ORGANIZATIONAL AGILITY, HUMAN RESOURCE FLEXIBILITY, AND ADAPTIVE LEADERSHIP ON EMPLOYEE RESILIENCE THROUGH THE MEDIATION OF PSYCHOLOGICAL CAPITAL (A CASE STUDY OF THE CARTON BOX DIVISION OF TJIWI KIMIA) - Ig Jarot Febri Setyo Wibowo (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study investigates the impact of organizational agility, human resource flexibility, and adaptive leadership on employee resilience, with psychological capital serving as a mediating variable, within the Carton Box Division of PT Pabrik Kertas Tjiwi Kimia Tbk. Operating in a highly dynamic and pressure-intensive manufacturing environment, organizations are required to develop adaptive capacities that sustain both performance and employee well-being. This research employs a quantitative explanatory design, utilizing data collected from 192 respondents selected through purposive sampling. The analysis is conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The findings reveal that organizational agility, HR flexibility, and adaptive leadership significantly and positively influence employee resilience. Psychological capital emerges as the most dominant predictor and plays a critical mediating role in translating organizational characteristics into individual adaptive capacity. The structural model demonstrates strong explanatory power, with R² values of 0.689 for psychological capital and 0.784 for employee resilience. These results confirm that adaptive organizational environments foster positive psychological states—comprising hope, efficacy, resilience, and optimism—which in turn enhance employees’ ability to withstand and recover from work-related pressures. This study contributes to the literature by integrating dynamic capabilities, human capital architecture, adaptive leadership, and psychological capital frameworks within a single model, particularly in the context of rigid manufacturing systems. Practically, the findings highlight the importance of human-centered organizational strategies in building sustainable workforce resilience. Organizations are encouraged to promote agility, implement flexible HR practices, and develop adaptive leadership to strengthen employees’ psychological resources and long-term performance sustainability.